The effects of integrating a cereal rye cover crop with herbicides on glyphosate-resistant horseweed (Conyza canadensis) in no-till soybean. Issue 5 (9th September 2020) - Essman, Alyssa I.; Loux, Mark M.; Lindsey, Alexander J.; Dobbels, Anthony F.; Regnier, Emilie E.
Abstract: Current recommendations for the control of glyphosate-resistant horseweed [ Conyza canadensis (L.) Cronquist var. canadensis ] in soybeans [ Glycine max (L.) Merr.] consist of comprehensive herbicide programs, which often include herbicide applications outside the soybean growing season. Integration of cover crops with herbicides could potentially improve C. canadensis control and allow for a reduction in herbicide inputs. Two separate field studies were conducted from 2016 through 2018 with the objectives of: (1) determining the effect of planting date and seeding rate of a cereal rye ( Secale cereale L.) cover crop on C. canadensis population density and control in the subsequent soybean crop; and (2) determining whether the cover crop could replace a fall herbicide treatment or allow for a reduction in the use of spring-applied residual herbicides. There was no effect of rye planting date, late September versus late October, on C. canadensis density in either study. In 2016 to 2017, C. canadensis density was greater in the absence of a rye cover crop in both studies, but otherwise not affected by seeding rates of 50 versus 100 kg ha −1 . In the 2017 to 2018 season, the presence of rye resulted in an increased C. canadensis density in the spring residual herbicide study (Study I), and had no effect in the fall herbicide study (Study II). Conyza canadensis densities were lowest in the treatments where a comprehensive spring residual or fall herbicide treatment had been applied, averaged over rye planting date and seeding rate. Earlier-planted rye at a higher seeding rate produced the most biomass but did not result in lower C. canadensis densities. These results suggest that cereal rye planted at a density of 50 kg ha −1 as a cover crop before no-till soybeans may be sufficient to reduce glyphosate-resistant C. canadensis plant density, but cannot be relied upon to reduce the need for fall herbicide treatments and spring residual programs.